Preservation of genetic resources by seed storage - Ng, N.Q. (1996)
Several ways exist of maintaining the genetic resources of crops. The cheapest and most convenient way is by storing seeds. However, not all crops can be preserved by storing their seeds, because they are either vegetatively propagated and/or do not produce seeds, or the period of their seed viability is short. Maximizing the longevity of seeds requires a good seed store and knowledge of the principles of seed preservation. This document discusses types of seed, techniques for preparing seeds for storage, factors controlling longevity of seed, standards of seed stores for genetic resources conservation, and design of seed stores.